Desarrollo de la competencia comunicativa en preparatorianos mexicanos durante la pandemia, estudio etnográfico - Terrazas-Medina, Tamara Isabel (2022)
The objective of this study: to know the way in which the development of communicative competence was promoted in Mexican high school students via remote education in the context of the Covid-19 pandemic. Research was qualitative and ethnographic. Sample: twenty students from four different high schools, from a public university in the northeastern of Mexico. Data collection was through semi-structured interviews and non-participant observations. Among the most relevant results, it was found that, even when teachers promoted communicative conditions for academic interaction, students did not want to do so; there was confusion in the remote classrooms regarding the correct alignment of the teaching and learning processes, which could have caused problems for students and teachers. It was concluded that educational training in special situations requires different preparation of teachers and students, according to the needs of times and special contexts in which they are educating.